THE INFLUENCE OF SERVICE QUALITY, PRICE, AND PROMOTION ON CONSUMER PURCHASING DECISIONS AT BMA PUTRA CARWASH - Akbar, Taufik; Sanida, Nuris (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
The fierce rivalry within the car wash service sector demands that businesses owners to understand the key factors influencing consumer purchase decisions to ensure business sustainability. The purpose of this study is to examine how pricing, promotions, and service quality affect customers' decisions to buy from BMA Putra Carwash. A quantitative method of study was used. Although the precise quantity remained unclear, the population was made up of all clients who have used BMA Putra Carwash services. Purposive sampling was therefore used to choose the sample, and 100 respondents were obtained by applying the Lemeshow technique to establish the sample size with a 10% margin of error. A Google Forms-distributed online survey was used to gather data. Multiple linear regression was used in the data analysis to see how various independent factors affected the dependent variable. Furthermore, statistical tests such as the coefficient of determination (R2), t-test, F-test, validity, and reliability were performed. Results show that the purchase decision at BMA Putra Carwash is significantly affected by service quality, price, and promotion, both individually and collectively. Consequently, it is advised that BMA Putra Carwash consistently uphold and enhance service quality, focusing particularly on speed, friendliness, and customer satisfaction. Maintaining competitive pricing and optimizing promotion strategies are also crucial. These measures are expected to sustainably boost purchase decisions and support business growth in the future.